Nitric Oxide Donors 2005
DOI: 10.1002/3527603751.ch1
|View full text |Cite
|
Sign up to set email alerts
|

NO and NO Donors

Abstract: Nitric oxide (NO), a magic free radical gas molecule, has been shown to be involved in numerous physiological and pathophysiological processes. Among its diverse functions, NO has been implicated in the relaxation of vascular smooth muscle, the inhibition of platelet aggregation, neurotransmission (Viagra reverses impotence by enhancing an NO-stimulated pathway), and immune regulation [1]. It was named the molecule of the year in 1992 by Science and was the subject of the Nobel Prize in 1998. NO has limited so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Nitric oxide (NO) has been shown to inhibit biofilm formation and prompt biofilm dispersal in many gram‐negative and gram‐positive bacteria 81,82 . While NO has shown promise in biofilm dispersal, its gaseous reactive state and short half‐life (0.1−5 s) has made it difficult to develop therapies 85 . Nitroxides are long‐lived, stable free radical species that are crystalline at room temperature.…”
Section: Small Molecule Inhibitionmentioning
confidence: 99%
“…Nitric oxide (NO) has been shown to inhibit biofilm formation and prompt biofilm dispersal in many gram‐negative and gram‐positive bacteria 81,82 . While NO has shown promise in biofilm dispersal, its gaseous reactive state and short half‐life (0.1−5 s) has made it difficult to develop therapies 85 . Nitroxides are long‐lived, stable free radical species that are crystalline at room temperature.…”
Section: Small Molecule Inhibitionmentioning
confidence: 99%
“…It is worth mentioning that the role of NO in cancer therapy is not only that of enhancing tumor blood flow and oxygen supply [ 12 ] but also reversing chemotherapy resistance through the upregulation of efflux pumps [ 13 , 14 ]. Along this line of research, Maksimovic-Ivanic et al demonstrated that the hybridization of some drugs with NO, such as NO-NSAIDs and NO-HIV-PIs, promoted anticancer activity in a wide range of cancer cell lines and in in vivo models, invariably more potent, less toxic, lower dosing, and fewer side effects than the corresponding des-NO analogs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-biofilm properties of NO in P. aeruginosa are mediated by regulation of intracellular levels of the secondary messenger cyclic dimeric guanosine monophosphate (cyclic di-GMP), which plays a pivotal role in biofilm development; high levels facilitate biofilm formation, while low levels prompt biofilm dispersal (7, 14). However, the targeted and controlled delivery of NO to biological systems as therapies is a challenge due to the reactive nature and short half-life (0.1 – 5 seconds) (15) of the gaseous molecule. Consequently, methods for circumventing this challenge have been the focus of intensive research over the past several years, with the use of NO-donors in biofilm dispersal now comprehensively documented (16, 17).…”
Section: Introductionmentioning
confidence: 99%